THE ANCIENT WHEATS OF GEORGIAAND THEIR TRADITIONAL USE IN THE SOUTHERN PART OF THE COUNTRY - Jorjadze, M.; Berishvili, T.; Shatberashvili, E. (Emirates Journal of Food and Agriculture, 2013)
Georgia represents a biodiversity hotspot for wheat with high levels of endemism. Many local variations of wheat are found in the country due to its variable climatic, edaphic, socio-economic and cultural landscape. Local variations of seven free-threshing and seven hulled wheat landraces and old varieties are found in the country, along with wheat utilization and the different traditional uses, are described in this paper. Despite the diversity and significance of Georgian wheats, their role in the wheat phylogenesis has not been thoroughly studied and the general public is not well informed on the subject. This article aims to promote Georgian wheat landraces and underline the necessity of carrying out a detailed systematic inventory of the wild and cultivated plants in Georgia order to get more information on the state of this national heritage and of the measures to be taken for its conservation.